SWEAR WORDS USED IN THE MOVIE “DO REVENGE” - Oktaviana Rewu; Mirsa Umiyati; I Made Astu Mahayana (Universitas Warmadewa, 2026)
The title of this research is “Swear Words Used in The Movie Do Revenge”. It aimed to analyze the types and motives of swear words found in the movie. This research used descriptive qualitative method. The data were taken from Do Revenge movie. In analyzing the data, the main theory proposed by Magnus Ljung in his book entitled “Swearing: A Cross-Cultural Linguistic Study” (2011) was used to analyze the types of swear words, and theory from Karjalainen journal “Where have all the swear words gone?” which contain Anderson theory (in 2002: 24) was used to classify the motives. Based on the results, it was found that there were five types of swear words such as, religious or supernatural, scatological, sex organ, sexual activities, and mother (family). Then there were three motives of swear words found such as, psychological motives, social motives, and linguistic motives.